Bibliometric analysis of breast cancer-related lymphedema research trends over the last 2 decades - Huang, Jinghui; Li, Jiamin; Li, Ying; Huang, Lele; Li, Bai; Huang, Feng; Lv, Can; Fang, Fanfu (Frontiers in Oncology, 2024)
As breast cancer cases rise globally, post-mastectomy lymphedema garners increasing scholarly attention. This study aims to conduct a comprehensive bibliometric analysis of Breast Cancer-Related Lymphedema (BCRL) research from 2003 to 2022, identifying trends and providing global research insights for future studies. Method: The literature for this analysis was extracted from the Web of Science (WoS) Core Collection, encompassing 1199 publications, including 702 articles and 101 reviews, totaling 803. Using advanced bibliometric tools such as VOSviewer and CiteSpace, quantitative and visual analyses were performed to map collaboration networks, research clusters, and emerging trends. The search strategy included specific terms related to lymphedema, breast cancer, and BCRL, ensuring a comprehensive representation of the research landscape.The bibliometric analysis revealed a steady increase in BCRL publications over the studied period, reaching a peak in 2018. The United States emerged as the leading contributor to BCRL literature, with China also demonstrating a significant presence. Collaboration networks were visualized, showcasing the interconnectedness of institutions and researchers globally. Key research hotspots identified include preventive strategies, complex decongestive therapy, and reconstructive interventions.In conclusion, this pioneering bibliometric analysis provides a comprehensive overview of BCRL research trends and collaborations globally. The findings contribute valuable insights into the evolution of the field, highlighting areas of focus and emerging research themes. This study serves as a foundational resource for researchers, clinicians, and policymakers, fostering evidence-based practices and interventions for BCRL in the future.